Focal segmental glomerulosclerosis lagged behind the onset of rheumatoid arthritis by 7 years: A case report and literature review. Issue 1 (January 2017) - Liu, Yang; Wen, Hong-yan; Wang, Li-hua; Wang, Chen
Abstract: Introduction: The co-existence of focal segmental glomerulosclerosis (FSGS) and rheumatoid arthritis (RA), presenting either together or in succession, is very rare. A variety of histopathological features in the clinical renal disease may occur in RA. Only 8 studies have previously reported this poorly understood connection. Clinical findings/diagnoses: A case of a 54-year-old male with RA lasting for more than 7 years developed cheirarthritis as the first signs. Symmetric polyarthralgia and multiple swollen joints throughout the body were followed, accompanied with morning stiffness. Gradually, he suffered from albuminuria, hypoalbuminemia, edema, and hyperlipidemia in 2014. The patient had the history of administering loxoprofen, celecoxib, leflunomide, and methotrexate. He was diagnosed as RA, nephrotic syndrome. Renal biopsy confirmed FSGS. Conclusion: Our case and the review of the literature indicate that FSGS is one of the causes of nephrotic syndrome in RA. It strongly suggested that RA patients with the abnormal kidney functions should be routinely screened for FSGS to guide the therapy, achieve both RA and FSGS remission, determine a prognosis, and avoid end-stage renal lesion.